Interleukin-17A promotes the differentiation of bone marrow mesenchymal stem cells into neuronal cells. (April 2021) - Chen, Hanlin; Li, Shasha; Xu, Wanting; Hong, Yongfeng; Dou, Rengang; Shen, Hongtao; Liu, Xue; Wu, Tingting; He, Jia Cai
Highlights: 20 ng/mL is the optimum concentration of IL-17A to promote neuronal differentiation of BMSCs. IL-17 promotes cell morphological changes and neural differentiation-related gene expression. IL-17 promotes neuronal differentiation in BMSCs through Wnt and Notch pathways. Abstract: Ischemia or hemorrhagic stroke is one of the leading causes of death and permanent disability in the worldwide population. As a consequence of the potential increasing in stroke, stem cell therapy is currently an area of intense focus. However, there are less data available regarding the promotion of healing efficacy after stroke. The present study aimed to investigate whether the cytokine interleukin-17A (IL-17A) could have a role in promoting the neuronal differentiation of mesenchymal stem cells (MSCs) and to investigate the associated molecular mechanism. Firstly, different concentration of IL-17A at range from 5−40 ng/mL was applied to stimulate bone marrow MSCs (BMSCs) during the course of neurogenic differentiation. Then reverse transcription-PCR, histological analyses and immunofluorescence assays were used to determine the optimum concentration of IL-17A in promoting the neuronal differentiation of BMSCs, which was 20 ng/mL. Mechanistically, Wnt signaling pathway was activated and Notch signaling pathway was suppressed. In addition, there were antergic effect of these two signaling pathways modulating the neurogenic differentiation of BMSCs induced by IL-17A. The present study demonstrated the potential role of IL-17A-based BMSCs strategy for promoting neuronal differentiation in vitro . However, the treatment efficacy could be considerably confirmed in animals with ischemia stroke. Therefore, a more sophisticated strategy that addresses the complicated treatment associated with stroke is needed.